Relative measurement and extrapolation of the scintillation quenching factor of $$α $$ α -particles in liquid argon using DEAP-3600 data - DEAP Collaboration (European Physical Journal C: Particles and Fields)
Abstract The knowledge of scintillation quenching of $$α $$ α -particles plays a paramount role in understanding $$α $$ α -induced backgrounds and improving the sensitivity of liquid argon-based direct detection of dark matter experiments. We performed a relative measurement of scintillation quenching in the MeV energy region using radioactive isotopes ( $$^{222}$$ 222 Rn, $$^{218}$$ 218 Po and $$^{214}$$ 214 Po isotopes) present in trace amounts in the DEAP-3600 detector and quantified the uncertainty of extrapolating the quenching factor to the low-energy region.